“Sensor-cloud”: Offering Useful Data Reliably to Mobile Cloud from Wireless Sensor Network - Mathapati, Mahantesh; Patil, Kavita K; Metan, Jyoti; Chandramohan, B (International Journal of Computer Sciences and Engineering, 2025)
The integration of wireless sensor network (WSN) and Mobile cloud computing (MCC) is a research topic that is attracting growing interest in both academia and industry. In this new paradigm, WSN provides data to the cloud, and mobile users request data from the cloud. This paper first identifies the critical issues that affect the usefulness of sensory data and the reliability of WSN, then proposes a novel WSN-MCC integration scheme named TPSS, which consists of two main parts: 1) TPSDT (Time and Priority based Selective Data Transmission) for WSN gateway to selectively transmit sensory data that are more useful to the cloud, considering the time and priority features of the data requested by the mobile user; 2) PSS (Priority-based Sleep Scheduling) algorithm for WSN to save energy consumption so that it can gather and transmit data in a more reliable way.